PERANCANGAN ALAT PRESS UNTUK FIBERBOARD (DITINJAU DARI KERAPATAN DAN KADAR AIR) - Meidinariasty, Anerasari (KINETIKA, 2018)
Fiberboard is a product made from wood or other lignocellulosic materials that is combined with synthetic adhesive and then processed by pressing. Corn cobs, coconut fiber, sawdust, and coffee bean pulp are lignocellulosic materials that can be used as raw materials for particle board. The manufacture of fiberboard is carried by variation of the raw material composition and variation of the additive which is used to know their effects on particle board quality based on SNI Standard 03-2105-2006. The manufacture of particle board was done with press machine. From the result of the analysis, it was found that variations of raw materials composition can affect the physical properties of the fiberboard. Physical properties parameters such as density and moisture content have fulfilled the standards of SNI 03-2105-2006. The best treatment in the manufacture of fiberboard is found on the composition of 70% corn cobs:30% coco fiber and 70% coffee bean pulp:30% sawdust seen from its high density and low moisture content value of the entire fiberboard produced